A reconstrução do caso de “La Tregua” em El Salvador: uma perspectiva conceitual - Reyes, Nohel Mario Meléndez (2019)
Currently the Nation-States are experiencing a process of refutation of the internal monopoly on legitimate violence, as well as of their traditional concept of sovereignty. The emergence of non-state actors who take de facto control in a part of the national territories is increasingly common. Forcing States to plan different types of strategies so as not to lose their legitimacy and presence in those controlled spaces. In this context, this dissertation aimed to study the phenomenon popularly known as La Tregua in El Salvador. This was a negotiation experience between the Salvadoran government through a mediating team, and the main three criminal organizations to decrease the number of homicides. The main categories that constituted the theoretical reference of this effort were those of public order, criminal organizations, criminal justice system, gangs and public policies. To carry out this research, a qualitative methodology based on the epistemological premises of symbolic interactionism was adopted. Likewise, the Secondary Analysis of Qualitative Data was used as the main interpretation tool. In this sense, the main sources of data were the news from investigative journals, the academic papers about the object of study and the official information of the government of El Salvador. As a result, the reconstruction of the main public actions against gangs in El Salvador was carried out, establishing the period 2003-2009. Secondly, were identify the elements that constituted the direct antecedents for the appearance of the phenomenon of study, establishing as temporal period the years 2009-2011. Finally, a reconstruction of the opaque process of negotiation between the Salvadoran government and the main criminal organizations in the country was made, establishing the period of this actions for the years 2011-2015.